ANALISIS KADAR VITAMIN C PADA KUBIS MERAH (Brassica oleracea L. var capitata) YANG DIBUAT JUS DENGAN VARIASI LAMA PENYIMPANAN - Siska Nur Aini; Crescentiana Emy Dhurhania (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Vitamin C is an antioxidant that is contained in red cabbage (Brassica oleracea L. var capitata). Generally, people store juice ingredients in the refrigerator. This research was carried out to determine the effect of storage time on vitamin C levels in juiced red cabbage. The variation of storage time used was 1, 4, and 7 days with a storage temperature of 5 oC. Qualitative test using iodine, Fehling, and ammonium molybdate reagent gave positive results containing vitamin C. The quantitative test was carried out by UV-Vis spectrophotometry at a maximum wavelength of 570.5 nm with operating time at 20 minutes after the test solution was added with H2SO4 and ammonium molybdate. The quantitative test results showed that the level of vitamin C on the first day was 63.92 mg / 100 g, on the fourth day was 63.32 mg / 100 g, on the seventh day was 62.52 mg / 100 g red cabbage with coefficients of variation 0.26%. The Tukey test resulted in a p value of more than ??0.05, ie 0.831, so that the levels of vitamin C red cabbage juice made on the 1st, 4th, and 7th days were not significantly different.